Analisis Yuridis Kebolehan Menteri Untuk Tidak Mengundurkan Diri Ketika Mengikuti Pemilu Dan Pilkada - Alexander Salim; Tri Susilowati (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Minister is one of the strategic positions in the government and state governance system in Indonesia. So the Constitutional Court Decision Number 85/PUU-XX/2022 which gives space to the Minister not to resign even though he is participating in the General Election or Regional Head Election, is a wrong decision which has been widely criticized by the public. Based on this, this research was carried out in order to analyze the extent of the role of the Constitutional Court in pursuing policy concepts in deciding cases regarding judicial review of the Constitution. This research uses normative legal research, with a conceptual approach, and analyzed using qualitative methods. The results of this research are that the Minister's failure to resign will greatly affect the implementation of state affairs and will cause the people to delegitimize the government which threatens the stability of the state.